Analysis of System Reporting and Validation in DC Microgrid DSC Research: An Ex Post Facto Reproducibility Study - Hidayat, Khusnul; Afandi, Arif Nur; Elmunsyah, Hakku; Sendari, Siti (Universitas Panca Marga, 2025)
Distributed secondary control (DSC) is essential for voltage regulation and current sharing in DC microgrids with high renewable penetration. However, the diversity of system configurations, control strategies, and validation approaches challenges the reproducibility of published results. This study evaluates reporting and validation practices in 74 DSC-related articles from a reproducibility and research ethics perspective. Using a document-based ex post facto design, we construct a Reproducibility Readiness Index (RRI) based on system configuration reporting, validation completeness, and performance metric clarity. Results show that most studies exhibit low to medium reproducibility readiness, with only about one third achieving high levels. While system descriptions are generally adequate, validation setups and performance metrics are often incomplete or qualitative. Studies including hardware-in-the-loop or prototype experiments tend to score higher, though weak documentation remains a major limitation. These findings emphasize reproducibility as both a technical and ethical concern and support the need for stronger transparency and open science practices in DSC research on DC microgrids.